Digital content analysis of the transformation of art appreciation through augmented reality in art exhibitions: Analisis konten digital terhadap transformasi apresiasi seni melalui augmented reality dalam pameran seni - Pradita, Shatiya Fahlevi; Fanani, Iqbal; Latifah, Rahma; Anggraeni, Sefina Nada (Universitas Negeri Yogyakarta, 2025)
This study analyses the transformation of art appreciation through Augmented Reality (AR) in art exhibitions using digital content analysis methods. Data were collected from social media, blogs, and discussion forums, and then coded qualitatively (Taguette and manually). The results identified three main themes: aesthetic experience, emotional engagement, and technical challenges. AR was found to create immersive and interactive experiences, enriching the appreciation of digital art. However, challenges such as technological access gaps and device limitations impact the quality of the experience. These findings highlight the need to harmonise technical and artistic aspects to optimise the use of AR in art in the digital age. _______________________________________________________________________________ Penelitian ini menganalisis transformasi apresiasi seni melalui Augmented Reality (AR) dalam pameran seni dengan metode analisis konten digital. Data diambil dari media sosial, blog, dan forum diskusi, lalu dikodekan secara kualitatif (Taguette dan manual). Hasilnya mengidentifikasi tiga tema utama: pengalaman estetis, keterlibatan emosional, dan kendala teknis. AR terbukti menciptakan pengalaman imersif dan interaktif, memperkaya apresiasi seni digital. Namun, tantangan seperti kesenjangan akses teknologi dan keterbatasan perangkat memengaruhi kualitas pengalaman. Temuan ini menyoroti perlunya harmonisasi aspek teknis dan artistik agar pemanfaatan AR dalam seni dapat optimal di era digital.